A Qualitative Exploration of Gaps and Challenges in Knowledge and Practices of Electroconvulsive Therapy by Key Personnel in Public and Private Mental Health Units in Kenya - Ali, Nabila Amin; Owiti, Frederick; Kigamwa, Pius; Kumar, Manasi (Frontiers in Psychiatry, 2019)
Evidence based research for ECT practice in Kenya is scarce. Seemingly this has stifled knowledge with regards to ECT practice among key personnel in the country. Research show that evidence based guidelines not only harmonizes clinical practice in a certain region but also improves health outcomes and quality of clinical decisions made by key personnel. This study aimed at assessing knowledge and administration of ECT by key personnel in psychiatric units in Kenya. This was a thematic qualitative study which was undertaken in 3 counties; Nairobi, Nakuru and Eldoret. Snowballing sampling method was used to get 33 targeted respondents who work in ECT department in both private and public facilities. Researcher designed respondent profile questionnaire and interview guides were used as study tools. Data collected was transcribed from the audio recordings. Content thematic qualitative analysis was done based on the patterns that were noted across the data collected. Findings were presented in form of themes which were illustrated through verbatim quotations. In general key personnel were knowledgeable about ECT in the different stages of the procedure but there were methodological incongruence in their practice with regards to pre-ECT preparation, stimulus dose calculation, and adequacy of seizure and in the procedure for dose adjustment of psychotropic medication before and after ECT sessions. The identified barriers to the uptake of evidence based practice were lack of infrastructure, inadequate funding, lack of adequate training and negative perception by patients, relatives and even some participants. Though key personnel in this study showed that they had knowledge on ECT administration, lack of standard guidelines on ECT practice led to lack of standardized training on the procedure hence the methodological incongruence. Inadequate infrastructure, knowledge and negative perception towards the procedure seemed to interfere with uptake of ECT as an intervention. The study therefore recommends: Adoption of a guideline by psychiatrists, Intense Training on ECT for the psychiatrists and registrars and specialized training for nurses on ECT. Funding should be made available to improve infrastructure in general. Finally awareness should be created on ECT to help deal with negative perception towards the intervention.